Mediation of Student Loyalty on the Influence of Service Quality and Institutional Image on Student Word of Mouth in Indonesia. - Ririn Andriana; Widji Astuti; Edi Subiyantoro (Dinasti Publisher, 2022)
Vocational High School competition is very tight, all institutions offer their own advantages to attract students. This study begins with the concept of Student Loyalty which is used to describe the mediator that links Service Quality and Institutional Image to WOM. Using the theory SERVQUAL by Parasuraman et al. (1991), the researchers used the Path Analysis model with SPSS 18. The number of respondents was 190 identified from 17 Vocational High Schools in East Java Province, Indonesia. The results show that Student Loyalty was unable to play a mediating role in the effects of Service Quality and Institutional Image on Word Of Mouth, and Institutional Image has a greater influence than service quality. Implications are discussed, and study limitations are noted for guidance in future research.